2003
DOI: 10.1002/ffj.1143
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil composition of Callistemon viminalis leaves from India

Abstract: The leaves of Callistemon viminalis, on hydrodistillation, gave 0.45% of an oil on a fresh weight basis. GC and GC-MS analysis of the oil resulted in the identification of 42 constituents, representing 99.5% of the oil. 1,8-Cineole (61.7%), α-pinene (24.2%) and menthyl acetate (5.3%) were the major components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 7 publications
(8 reference statements)
0
24
0
2
Order By: Relevance
“…Studies carried out with plants of this same species collected in Brazil and in other countries resulted in lower yields of essential oil from the leaves than that observed in this work. Srivastava et al [15] evaluated the essential oil from the leaves of C. Viminalis collected in India and obtained a yield of 0.45%. Oyedeji et al [16] found 0.90% of the essential oil in leaves of plants collected in South Africa.…”
Section: Resultsmentioning
confidence: 99%
“…Studies carried out with plants of this same species collected in Brazil and in other countries resulted in lower yields of essential oil from the leaves than that observed in this work. Srivastava et al [15] evaluated the essential oil from the leaves of C. Viminalis collected in India and obtained a yield of 0.45%. Oyedeji et al [16] found 0.90% of the essential oil in leaves of plants collected in South Africa.…”
Section: Resultsmentioning
confidence: 99%
“…C. viminalis is edible,and its leaves are a tea substitute and have a delightfully refreshing flavour and fragrance. Antihelminthic and antibacterial activities of C. viminalis various parts have been reported [8]. It has been used to prepare a hot drink locally referred to as “tea” for the treatment of gastroenteritis, diarrhea and skin infections [9].…”
Section: Introductionmentioning
confidence: 99%
“…In Cameroon and particularly in the town of Dschang (West Cameroon), it is found along major roads and near homes. The EO from leaves of C. viminalis presented anthelmenthic effects while the aqueous extracts of flowers and leaves have antibacterial effects against gram‐positive bacteria (Srivastava et al. 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In Cameroon and particularly in the town of Dschang (West Cameroon), it is found along major roads and near homes. The EO from leaves of C. viminalis presented anthelmenthic effects while the aqueous extracts of flowers and leaves have antibacterial effects against gram-positive bacteria (Srivastava et al 2003). In our continuous search for new strategies to protect stored grains against insect infestation by using biopesticides (Tapondjou et al 2003(Tapondjou et al , 2005Ndomo et al 2008), the EO from the leaves of C. viminalis was evaluated for its insecticidal activities against A. obtectus and C. maculatus in bean and cowpea grains respectively.…”
Section: Introductionmentioning
confidence: 99%